2016
DOI: 10.1136/bjophthalmol-2015-307955
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids as a therapy for bacterial keratitis: an evidence-based review of ‘who, when and why’

Abstract: Corticosteroids have been proposed as an adjunct to antibiotics for the treatment of bacterial keratitis, with significant controversy regarding the appropriate use of this therapy. Recent prospective randomised controlled trials have provided additional evidence to guide clinical decision-making. A review of the epidemiology and mechanisms of pathogenesis, preliminary animal studies, retrospective human studies and prospective randomised clinical trials that address the potential risks and benefits of cortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 71 publications
0
16
0
1
Order By: Relevance
“…Corticosteroid therapy is used with the aim of reducing the host inflammatory response initiated by bacterial toxins and the lytic enzymes released by PMN, which obstructs corneal healing after infection [66]. However in P. aeruginosa keratitis, corticosteroid treatment may slow corneal wound healing, extend the infection period and induce stromal thinning and perforation.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Corticosteroid therapy is used with the aim of reducing the host inflammatory response initiated by bacterial toxins and the lytic enzymes released by PMN, which obstructs corneal healing after infection [66]. However in P. aeruginosa keratitis, corticosteroid treatment may slow corneal wound healing, extend the infection period and induce stromal thinning and perforation.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…In particular, topical corticosteroids are often used to reduce the host inflammatory response. Yet, controversy remains regarding the benefits and risks associated with this immunosuppressive therapy [ 9 , 10 ]. To this end, treatments are needed that both regulate the inflammatory response and promote corneal wound healing to resolve visual disturbances and improve quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Based on results of this pilot study, the Steroids for Corneal Ulcers Trial (SCUT) was initiated and published in 2012, and remains the largest randomized controlled trial on the topic to date [21]. In a recent review by Tallab and Stone [22], the authors concluded that, based on SCUT, there was level I evidence for a small benefit with the use of steroids in culture-proven non- Nocardia bacterial keratitis.…”
Section: Key Studiesmentioning
confidence: 99%